2010
DOI: 10.1007/s10237-010-0271-1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling cell entry into a micro-channel

Abstract: Cell entry into a micro-channel has potential applications in cell sorting and cancer diagnostics. In this paper, we numerically model breast cancer cell entry into a constricted micro-channel. Our results indicate that the cell velocity decreases during entry and increases after entry, an observation in agreement with experiments. We found that the cell entry time depend strongly on the cortical stiffness and is minimum at some critical cortical elasticity. In addition, we found that for the same entry time, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 43 publications
2
52
0
Order By: Relevance
“…As the front of the cell gradually leaves the micro-channel, it restores its original structure with increasing velocity. Those results are agrees with experimental observations [138] and the results obtained from compound drop model [153]. The obtained patterns of cell deformation, contraction and expansion as well the recovery of its original shape are similar to experimental observations.…”
Section: Movement and Deformation Of Single Cellssupporting
confidence: 82%
See 1 more Smart Citation
“…As the front of the cell gradually leaves the micro-channel, it restores its original structure with increasing velocity. Those results are agrees with experimental observations [138] and the results obtained from compound drop model [153]. The obtained patterns of cell deformation, contraction and expansion as well the recovery of its original shape are similar to experimental observations.…”
Section: Movement and Deformation Of Single Cellssupporting
confidence: 82%
“…Recently, Leong et al presented a modified compound drop model, which can consider stiffness, elasticity, and viscosity of both the cortex and the nucleus to model breast cancer cell entry into a constricted micro-channel. The modeled cell entry behavior agrees with experimental observations [153].…”
Section: Movement and Deformation Of Single Cellssupporting
confidence: 79%
“…Experimental work on red blood cells [3] and polymeric capsules [7] has shown that changes in mechanical properties and cell radius determine the passage of the container and in some cases may induce capillary blockage [8,9]. Previous theoretical work has extensively studied the transient dynamics of elastic capsules in both cylindrical and rectangular constrictions [10][11][12], the production of smaller vesicles [13], and the translocation of vesicles through narrow pores [14].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, flat channel walls are well adapted to observe cell-surface interactions by optical microscopy during cell transit in a capillary. Efforts in modeling have been undertaken for the entry of a cell in a simple constriction, 45,46 but they omit leakage and friction effects. A microfluidic micropipette method was recently described to measure the cell cortical tension, but not the viscous properties, or loss modulus, of cells.…”
Section: Introductionmentioning
confidence: 99%